Dispositivos móveis como suporte pedagógico nas práticas de leitura em sala de aula com alunos do ensino fundamental II - Vitali, Claudia Fumaco (2020)
This research was carried out in the Graduate Program in Education, Doctoral Course in Education, in the line of research Public educational policies, educational practices and their interfaces. It deals with the investigation of the potential of mobile devices as a pedagogical support in classroom reading practices, especially with the smartphone device, with students in the ninth grade of elementary school at a Municipal School in the city of Porto Alegre-RS. The focus of this research is centered on school practices, reading, through the digital reading application using the Kobo application. The general objective was to investigate how mobile devices in Portuguese language classes in the final grades of elementary school II may or may not contribute to the development of reflective school reading practices. The research had as specific objectives: to research possible applications for the development of school reading on smartphones, to develop school reading practices in the ninth grade of Elementary School II using applications on smartphones, analyze whether the practices developed in the classroom, with school reading , via the mobile device (smartphone) contribute or not to the development of the act of reading, analyzing and reflecting on the practices developed during the research through the data, perceptions and responses collected during the course of the study and analyzing the development of reflective reading from digital reading. The methodological perspective was Action Research, presented in two cycles: the first in a pilot format, in a private school and the second, which was the main focus for the final analysis and reflections, in a public school. As final reflections and conclusions, we highlight the great ease with which students use the smartphone for their leisure and a certain resistance to using it for educational purposes. Classroom reading practices need to have a real meaning for the student's world and no longer be a mere decoding of letters and words. We also found that, in addition to the need for a technologically equipped school, the entire system that encompasses education needs to go together. The school, the teacher and the students need to be aligned in a single process. Technology alone will not be able to act as a transforming action in education.